2015
DOI: 10.1186/s12872-015-0025-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of endovascular treatment for patients with TASC II D femoropopliteal occlusive disease: a single center study

Abstract: BackgroundAdvances in endovascular technology led to an alternative treatment option for TASC II D (TransAtlantic Inter-Society Consensus II class D) lesions. This study was aimed to evaluate the outcomes of endovascular treatment for TASC II D femoropopliteal lesions.MethodsEndovascular intervention with bare nitinol stent implantation was performed on 58 limbs (53 patients) with TASC II D femoropopliteal lesions from January 2011 to March 2013. Kaplan-Meier curves of primary patency, assisted patency and sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Although endovascular approach in the aortoiliac segments results in excellent acute and acceptable long-term patency, procedures in the femoropopliteal and particularly in the infrapopliteal segments are still hampered by high rates of restenosis, which is the major drawback of this technique and still an unmet challenge. 12 Antiproliferative drug-eluting devices have been shown to reduce the rate of restenosis in the femoropopliteal segments; their beneficiary effect for treatment of lesions below the knee, however, has not been demonstrated yet. We also prefer drugcovered/coated balloons for distal lesions resistant to initial PTA.…”
Section: Discussionmentioning
confidence: 99%
“…Although endovascular approach in the aortoiliac segments results in excellent acute and acceptable long-term patency, procedures in the femoropopliteal and particularly in the infrapopliteal segments are still hampered by high rates of restenosis, which is the major drawback of this technique and still an unmet challenge. 12 Antiproliferative drug-eluting devices have been shown to reduce the rate of restenosis in the femoropopliteal segments; their beneficiary effect for treatment of lesions below the knee, however, has not been demonstrated yet. We also prefer drugcovered/coated balloons for distal lesions resistant to initial PTA.…”
Section: Discussionmentioning
confidence: 99%
“…Korkmaz et al reported a primary patency rate of 84% and freedom from re-intervention for 8 years at a 76% rate in a similar singlecenter study (8). Another study done by Guo et al showed a successful revascularization rate of 95% and a 77% firstyear primary patency rate for the TASC II D lesions (7,9). These results together seem promising and a prediction of the shift from open surgery to newer endovascular techniques doesn't seem unreasonable.…”
Section: Discussionmentioning
confidence: 96%
“…Our study had some limitations with the length of followup period being the most important one. Data from other similar papers suggest that risk of re-occlusion and the need for re-intervention increases with time therefore studies with long-term follow-ups can show the patency rate more accurately (8,9,11). Another limitation was the study being carried out in a single center without the diversity of equipment and expertise therefore not representing a bigger population.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent updates to the guidelines (TASC II) concur with our conclusion that when anatomy is suitable or the patient is a poor operative candidate, endovascular intervention should be attempted prior to open bypass. [17][18][19] This study supplements the data available to guide decisionmaking regarding repeat revascularization after previous failed endovascular therapy. Current literature gives conflicting views on best approach after failed endovascular intervention.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent updates to the guidelines (TASC II) concur with our conclusion that when anatomy is suitable or the patient is a poor operative candidate, endovascular intervention should be attempted prior to open bypass. 17 -19…”
Section: Discussionmentioning
confidence: 99%